P317 The study of available and promising methods of diagnosis, correction and treatment of fetal ovarian tumors (Cysts) in the fetus, with maximum preservation of the function of the reproductive system. the study was formed by the leading doctors of the perinatal center of the st. petersburg state pediatric medical university. (June 2019) - Taits, Anna; Ivanov, Dmitriy; Malisheva, Anna; Errshov, Ivan
Abstract : The most frequent complication is the twisting of the legs of an ovarian cyst in 61% cases, intestinal obstruction in 3%. Twisting an ovarian cyst can spontaneously regress, but it can also cause embedding the appendages themselves and their migration to different parts of the abdominal cavity and cause sudden death of the newborn. Indications for surgical treatment are: the size of a cyst is more than 4 cm, signs of torsion, a migrating cyst. Materials and methods: In our study, there were 20 girls born on the term from 26 to 41 weeks of gestation, in 7 cases through cesarean section, and in 13 cases through the birth canal. 15 girls from the group of newborns diagnosed with prenatal from 30 to 36 weeks of pregnancy were hospitalized in the department of pathology of newborns and premature babies in the period from 1 to 5 days of life and 3 girls of infancy in 1-1.5-2 months of life, due to the fact that the diagnosis is made in a month of life. The examination of the girls included anamnesis, general clinical studies, an ultrasound examination of the pelvic organs and the abdominal cavity was performed. In 11 cases out of 20 additional multispiral computed tomography was required, as well as histological examination of the surgical material. Surgical treatment was performed on all girls with laparoscopic transumbulial minilaparotomy. All interventions were performed as far as possible with maximum preservation of ovarian tissue. In 12 girls, adnexectomy was performed due to necrotic changes of the appendages as a result of torsion of 45% and in combination with adhesive disease 15%. Ovariocytectomy was performed in 6 cases. And in 2 cases enterokistoma was detected. According to the morphological assessment of ovarian lesions in newborns, in most cases there are simple follicular ovarian cysts with hemorrhages, calcification and necrosis during torsion. Conclusions: Particular attention should be paid to quality prenatal diagnosis with a detailed assessment of all criteria for simple and complex ovarian cysts and the question of the possible use of fetal surgery, which will facilitate the timely adoption of measures and prevent the occurrence of complications with subsequent loss of appendages. An obstetrician-gynecologist should be involved at all stages of the management and treatment of this category of patients from the moment of prenatal diagnosis. Surgical treatment of these patients should be carried out in specialized hospitals using high-tech methods.